Note respecting the Royal Exchange, Edinburgh, and the Original List of Subscribers in 1752 (Proceedings of the Society of Antiquaries of Scotland, 1863)
In the early 18th century a fire destroyed the Royal Exchange building in Edinburgh. This article quotes original documents and historians’ opinions in order to discuss the proposal that a new Exchange should be built in 1752.